IMPACT OF E-COMMERCE ON INTERCULTURAL ASPECTS OF COMMUNICATION (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Digitalization of business in combination with cultural diversity has created a new space and conditions where communication becomes a challenge. The purpose of the article is to identify intercultural aspects of communication in the context of digital business development. It is established that cultural sensitivity in business involves, on one hand, the formation of respect for legal and moral norms specific to a particular community, and on the other hand, enhances the operational efficiency of the company. It is argued that cultural factors influence decision-making in international business, and awareness and knowledge of cultural differences enhance the competitiveness of the company. It is postulated that the intercultural competencies of managers should be viewed in terms of their new functions and socio-professional roles in transnational organizations and through the lens of their cultural intelligence, which facilitates adaptation to new cultural realities and cultural freedom—a set of necessary skills, knowledge, and abilities for a manager in an international and even global dimension. The top 10 countries in the Digital Technology Usage Index (NRI) reveal three trends: they belong to high-income countries, demonstrate reliable network readiness in all dimensions, and European countries continue to dominate the list. These trends persisted in the 2023 ranking.The challenges hindering the development of digital trends and the transformation of the Ukrainian economy into a digital one are substantiated. Two scenarios for the development of digital business in Ukraine are identified depending on the assessment of the criticality and necessity of changes in the traditional economic structure: the inertial (evolutionary) and the targeted (forced). In the case of implementing the inertial scenario, the Ukrainian economy will remain inefficient, labor migration will continue, and Ukrainian products will be non-competitive in external markets. The targeted scenario envisions the transition of the Ukrainian economy to a digital one within 3-5 years. The result will be the emergence of new norms, standards, and value systems. The internationalization of management changes the traditional model of management communications.
Keywords: business digitization, cultural diversity, cultural sensitivity in business, intercultural managerial competencies, NRI index, inertial (evolutionary) development scenario, target (forced) development scenario.